2021
DOI: 10.3389/fgwh.2021.656616
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care in Family Planning Services: Differences Between Formal and Informal Settlements of Kira Municipality, Uganda

Abstract: Background: Quality of care (QoC) of family planning (FP) affects contraceptive use, and it varies across types of urban settlement. This study assesses the difference in service delivery point (SDP) structural and process factors between formal and informal urban settlements, and the opinion of the client on the QoC in informal settlements. This is useful in creating an evidence base to advocate for better quality services for the most vulnerable in society.Methods: This was a cross-sectional survey that incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
(60 reference statements)
2
6
0
Order By: Relevance
“…On the other hand, studies from Jordan have reported lower odds of adequate counselling among government facilities [ 10 ]. However, some studies from Uganda, Ethiopia and Kenya, report findings similar to ours [ 28 , 39 , 42 ]. The predominant source of modern contraceptive methods in Sierra Leone is the public sector providing over 80% of all clients while the private medical sector covers only 18% of users [ 18 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…On the other hand, studies from Jordan have reported lower odds of adequate counselling among government facilities [ 10 ]. However, some studies from Uganda, Ethiopia and Kenya, report findings similar to ours [ 28 , 39 , 42 ]. The predominant source of modern contraceptive methods in Sierra Leone is the public sector providing over 80% of all clients while the private medical sector covers only 18% of users [ 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…In Sierra Leone, proportion of younger women receiving good quality FP counselling services is higher compared to findings from countries in Sub-Saharan Africa such as Kenya (56.7%), Uganda (34.9%) and Senegal (18%) [ 8 , 29 , 39 ]. Furthermore, studies from other regions in countries such as Nepal and Spain indicated that the quality of FP counselling services were low and unsatisfactory based on the patient expectations and experience thus demanding for more information about the different methods [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In concordance with the findings from previous studies [ 30 , 34 , 35 ], we found that most adolescent girls and young women in SSA do not receive quality contraceptive counselling. Perhaps, the ineffective implementation of sexual and reproductive health policy strategies [ 36 ] as well as the attitude toward contraceptive counselling [ 37 , 38 ] might have contributed to the limited access to quality contraceptive counselling among adolescent girls and young women in SSA.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have identified a range of factors that can promote or inhibit QC for family planning. 6,7,[10][11][12][13][14][15][16][17] However, these prior studies sometimes focused only on clients' or providers' perspectives or used survey methods that assume the factors are known well enough to be limited to closed-ended survey questions. Most of these other studies were also conducted in other countries.…”
Section: Highlightsmentioning
confidence: 99%